Avaliação de compostos bioativos e capacidade antioxidante do bagaço de uva - Iora, Sandra Regina Fernandes (2014)
Brazil, due to its large agricultural production, is one of the largest producers of agro-industrial waste worldwide and there is a growing interest in finding alternatives to the use of organic material generated, which currently has been a source of environmental pollution. Wine industry has generated a large amount of waste that may be a low cost and good profitability in technological applications, besides containing bioactive compounds of high commercial value. Grape pomace of three varieties was evaluated in current study. Fatty acids and phenolic compounds were identified respectively by gas and liquid chromatography. Antioxidant capacity of the phenolic extracts was determined by three different methods, namely DPPH, ABTS+ and ferrous ion assays. Cabernet Sauvignon pomace revealed the higher rates of total phenolic -1 -1 compounds (5,101.82 ± 119.03 mg GAE 100 g ), flavonoids (2,983.91 ± 51.76 mg CTE 100g ) -1 and monomeric anthocyanin (2,092.93 ± 71.57 mg mal-3-glu.100 g), coupled to lowest EC50 rates in DPPH and ABTS assays, showing a high antioxidant activity.